Effects of geogebra on students' attitudes and achievement in learning quadratic functions, equations and inequalities - Urgena, John Nico A. (Animo Repository, 2015)
The recently adopted K-12 mathematics curriculum in the Philippines suggests selected topics to be taught using technology. It has been proven in many researches that technology enhances students learning. This study sought to examine the effects of dynamic graphing freeware GeoGebra on students attitudes and achievement in learning quadratic functions, equations and inequalities. It made use of a quasi-experimental design. Seventy-five (75) Grade 9 students from a technical institute underwent GeoGebra activities and one hundred forty-two (142) students comprised the control group. Results showed that the GeoGebra group significantly outperformed the control group with large effect size (d = 0.92) on students achievement. An analysis of covariance indicated that space relation abilities as a covariate did not affect students posttest scores on items that are abstract. Students acceptance of GeoGebra on perceived ease of use, perceived usefulness, attitude towards usage and behavioral intention to use the system, were determined through an adapted survey anchored on Davis (1989) Technology Acceptance Model. Path analysis results suggest that students find GeoGebra effective as supported by the significant relationships between the constructs of TAM. Selected students who were interviewed find GeoGebra useful. They were motivated by the idea of guided explorations, as well as classroom discussions when they get to clarify and verify their discoveries.